A solvent-free epoxy curing agent and preparation method thereof
By designing suitable amine-based curing body, toughening agent and accelerator combination in solvent-free epoxy curing agent, combined with specific preparation methods and structural design, the problem of insufficient performance of curing agents in the prior art is solved, and the further development is achieved High mechanical properties, chemical resistance and heat resistance significantly improve the overall performance of the curing agent.
Patent Information
- Application Number
- CN202210619814.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-06-02
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2042-06-02
AI Technical Summary
Existing solvent-free epoxy curing agents have shortcomings in performance improvement, especially the impact of other components in the curing agent on performance is not fully utilized, resulting in poor performance in mechanical properties, chemical resistance and heat resistance. good.
By designing suitable amine-based curing bodies, toughening agents and accelerators, specific preparation methods are adopted, such as the preparation of benzyl polyamines and the preparation of polyamine-epoxy adducts, combined with paraffin and palm wax pretreatment and the preparation of cationic surfactants, as well as the toughening agent structure of perlite micropowder core, microcrystalline wax layer, rubber layer and plastic layer, improve the overall performance of the curing agent.
It significantly improves the temperature resistance, chemical resistance, curing performance and toughening effect of the curing agent, optimizes the dispersion and compatibility of the curing agent, and improves the hardness, adhesion, impact resistance and water resistance of the curing agent. Shorten the curing surface drying time.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of chemical coatings, and more specifically, relates to a solvent-free epoxy curing agent and a preparation method thereof. Background Art
[0002] Epoxy resin itself is a linear thermoplastic polymer. Uncured epoxy resin does not have good mechanical properties, chemical resistance and heat resistance. However, by reacting linear epoxy resin with a suitable curing agent to form a three-dimensional cross-linked thermosetting structure, good performance can be obtained. This process is usually called the curing or gelation process of epoxy resin. Therefore, the curing agent is the key to the practical application value of epoxy resin.
[0003] Epoxy curing agents can be divided into solvent-based and solvent-free types. The production of solvent-based epoxy curing agents is mainly due to the structure of epoxy resin, which makes it incompatible with water. It needs to add organic solvents such as benzene, ketones, and aromatic hydrocarbons as diluents. It has a strong odor and is easy to volatilize, causing great pollution to the surrounding environment. With the increasing requirements for environmental protection, the solvent-free, high solid content, and water-based epoxy curing agents are receiving more and more attention.
[0004] At present, the research on solvent-free epoxy curing agent mainly focuses on the modification of its curing main amine, but ignores the influence of other components in the curing agent on the performance of the curing agent. For example, toughening agent can effectively improve the flexibility of the cured product, and accelerator can not only reduce the reaction temperature and shorten the reaction time, but also improve the mechanical properties of the cured product.
[0005] In summary, how to provide a solvent-free epoxy curing agent and a preparation method thereof, and effectively improve the comprehensive performance of the curing agent by combining the amine curing main body and other auxiliary components in the curing agent, is a problem that urgently needs to be solved. Summary of the invention
[0006] The purpose of the present invention is to solve the above technical problems and provide a solvent-free epoxy curing agent and a preparation method thereof. The amine curing agent, toughening agent and accelerator in the curing agent are designed respectively, which can effectively improve the comprehensive performance of the curing agent.
[0007] The present invention achieves the above-mentioned purpose through the following technical solutions:
[0008] A solvent-free epoxy curing agent comprises the following raw materials in parts by weight: 50-100 parts of benzyl polyamine, 20-50 parts of polyamine-epoxy adduct, and 0-20 parts of accelerator.
[0009] The preparation method of the benzyl polyamine is as follows: polyamine, water, metal hydroxide and fatty alcohol are added to a four-necked reaction bottle, toluene monohalide is slowly added dropwise under a nitrogen atmosphere, and then the temperature is raised to 40-80° C. to react for 1-10 hours. After the reaction is completed, the benzyl polyamine is filtered, oil and water are separated, and vacuum distillation is performed to obtain the benzyl polyamine.
[0010] Wherein, the metal hydroxide is one of potassium hydroxide, sodium hydroxide, lithium hydroxide, calcium hydroxide and barium hydroxide.
[0011] The fatty alcohol is one of methanol, ethanol, propanol, isopropanol, n-butanol and isobutanol.
[0012] The toluene monohalide is toluene monochloride or toluene monobromide.
[0013] Furthermore, the promoter is selected from one of 2,4,6-tris(dimethylaminomethyl)phenol, benzyldimethylamine, triethylamine, triethanolamine, and o-hydroxybenzyldimethylamine, the molar ratio of polyamine, metal hydroxide, fatty alcohol, and toluene monohalide is 1:(0.8-1.2):(2-6):(0.7-0.9), and the mass ratio of metal hydroxide to water is 1:(3-5).
[0014] Furthermore, the preparation method of the polyamine-epoxy resin adduct is: take the polyamine into a four-necked reaction bottle, slowly add the epoxy resin dropwise under a nitrogen atmosphere, and then heat to 40-80°C for reaction for 1-6 hours. After the reaction is completed, the polyamine-epoxy resin adduct is obtained; the mass ratio of the polyamine to the epoxy resin is 1: (0.8-1.8).
[0015] The epoxy resin is selected from one of bisphenol A glycidyl ether, bisphenol F glycidyl ether, butyl glycidyl ether, phenyl glycidyl ether, allyl glycidyl ether, C12-C14 glycidyl ether and cardanol glycidyl ether.
[0016] All of the above polyamines are one or more of aliphatic amines, alicyclic amines and aromatic amine compounds containing two primary amine groups.
[0017] The present invention also provides a pretreatment method for the accelerator in the solvent-free epoxy curing agent, which specifically comprises the following steps:
[0018] (1) Add paraffin wax and palm wax to a solvent (40-50°C) and mix well, then add a cationic surfactant and mix well. The obtained oil phase is set aside;
[0019] (2) preheating the accelerator (50-60°C) and then adding it dropwise to the oil phase obtained in step (1) under stirring (2000-3000 r / min) to obtain an emulsion;
[0020] (3) The emulsion is dispersed in a disperser (400-600 r / min) and heated (65-75°C) to evaporate the solvent, thus completing the pretreatment of the accelerator.
[0021] Furthermore, in step (1), the melting point of paraffin is 50-60°C, the solvent is petroleum ether (boiling point is 60-70°C) or chloroform, and the mass ratio of paraffin, palm wax, solvent, and cationic surfactant is 1:(2-3):(4-8):(0.6-1.6); in step (2), the mass ratio of accelerator to oil phase is 1:(2-4).
[0022] Furthermore, the preparation method of the cationic surfactant is as follows: fatty acid, benzene and concentrated sulfuric acid are uniformly mixed in a reaction kettle, and then 2,3,4-trihydroxybutyric acid is added dropwise, and the mixture is reacted for 8-16 hours under heating (80-90°C) and stirring conditions, and then a mixed solution of anhydrous citric acid and thionyl chloride is added dropwise, and the mixture is reacted for 6-10 hours under heating (80-90°C) and stirring conditions, and 3-6 times the amount of deionized water is added to the obtained product, and after uniform mixing, ammonium bicarbonate is added for neutralization reaction, and the cationic surfactant is obtained after filtering and removing impurities; wherein the molar ratio of fatty acid, 2,3,4-trihydroxybutyric acid and anhydrous citric acid is (3-3.3):1:(1-1.4), the amount of concentrated sulfuric acid added is 2-3% of the fatty acid, the amount of thionyl chloride added is 0.5-1.5% of the anhydrous citric acid, and the fatty acid is a long-chain fatty acid.
[0023] The present invention also provides a toughening agent used in the solvent-free epoxy curing agent, wherein the mass fraction of the toughening agent in the curing agent is 10-20 parts, and the toughening agent is a core-shell structure, and comprises a perlite micropowder core, a microcrystalline wax layer, a rubber layer and a plastic layer from the inside to the outside, and the mass ratio thereof is 1: (1-2): (3-5): (1-3).
[0024] Furthermore, the raw materials for preparing the perlite powder core include perlite powder and silane coupling agent in a mass ratio of 1: (0.1-0.3); the raw materials for preparing the microcrystalline wax layer include microcrystalline wax and anionic emulsifier in a mass ratio of 1: (0.15-0.3); the raw materials for preparing the rubber layer include styrene, butadiene, diallylamine, and azobisisobutyramidine hydrochloride in a mass ratio of 1: (0.4-0.6): (0.2-0.4): (0.06-0.1); the raw materials for preparing the plastic layer include styrene, 3,4-epoxy-1-butene, methyl methacrylate, and redox initiator in a mass ratio of 1: (0.3-0.5): (1-1.6): (0.05-0.1).
[0025] Furthermore, the preparation method of the toughening agent is:
[0026] S1. Take perlite powder, add (5-10 times the amount) water and silane coupling agent, stir and soak for 30-60 minutes, then evaporate the water to obtain perlite powder core;
[0027] S2, stir the microcrystalline wax and anionic emulsifier evenly, place in an emulsifier (emulsification temperature is 85-95°C, stirring speed is 2500-3500r / min), add (10-20 times amount) of deionized water for emulsification, and obtain a microcrystalline wax emulsion;
[0028] S3, placing the pearlite powder core and the microcrystalline wax emulsion in a disperser at 110-120° C. and dispersing until the water evaporates to obtain a microcrystalline wax layer;
[0029] S4, adding a nonionic emulsifier (the amount added is 10-16% of the deionized water), deionized water (the amount added is 10-20 times of all the raw materials) and the material obtained in step S3 to the reactor, stirring evenly, adding monomers styrene, butadiene, and diallylamine, stirring to emulsify the monomers, and then adding azobisisobutylamidine hydrochloride ATNA as a cationic initiator, reacting at 60-65° C. for 8-12 hours to obtain a rubber layer;
[0030] S5, adding monomers of styrene, 3,4-epoxy-1-butene, and methyl methacrylate to the material obtained in step S4, stirring to emulsify the monomers, and then adding a redox initiator, reacting at 50-60° C. for 3-5 hours to obtain a plastic layer;
[0031] S6, freezing and demulsifying the material obtained in step S5, washing, filtering and vacuum drying to obtain a toughening agent product.
[0032] In step S1, the particle size of the perlite powder is 5-10 μm, and the bulk density is 40-70 kg / m 3 .
[0033] In step S2, the melting point of the microcrystalline wax is 65-75°C, and the anionic emulsifier is a carboxylate or a sulfonate.
[0034] In step S4, the nonionic emulsifier is a fatty alcohol polyoxyethylene ether series, an isomeric tridecanol polyoxyethylene ether series or an alkylphenol polyoxyethylene ether series.
[0035] In step S5, the redox initiator is benzoyl peroxide / N,N-dimethylaniline, ammonium persulfate / sodium bisulfite, cumene hydroperoxide / tetraethyleneimine or tert-butyl hydroperoxide / sodium pyrosulfite.
[0036] The present invention also provides a method for preparing the solvent-free epoxy curing agent, which specifically comprises the following steps:
[0037] A. Place the pretreated accelerator and nano-lignin powder in a disperser at 30-40°C and disperse for 1-2 hours to obtain material 1;
[0038] B. Mix lignin sulfonate, sodium silicate and water evenly, then add 0.2-0.4 times the amount of toughening agent and soak for 30-50 minutes, then heat and evaporate to obtain material 2;
[0039] C. Evenly mix the benzyl polyamine and the polyamine-epoxy adduct according to the mass fractions, and then add material 1 and material 2 to obtain a curing agent;
[0040] The mass ratio of the pretreated accelerator to the nano-lignin powder in step A is 1:(0.03-0.06), and the mass ratio of lignin sulfonate, sodium silicate and water in step B is 1:(0.1-0.4):(3-5).
[0041] The beneficial effects of the present invention are:
[0042] (1) During the preparation process of the curing agent of the present invention, benzyl polyamine is selected to introduce a benzene ring group, which can improve the temperature resistance and chemical resistance of the product.
[0043] (2) The present invention adds an accelerator and pre-treats the accelerator with paraffin wax and palm wax, which not only improves the stability of the accelerator so that the accelerator only exerts an accelerating effect during heating and curing, but also improves the dispersion effect of the accelerator in the curing agent, thereby improving the curing performance of the curing agent.
[0044] (3) The present invention prepares a cationic surfactant with multi-lipophilic side chains, which can promote the aggregation of paraffin wax and palm wax in the emulsion on the surface of the promoter droplets, thereby completing the pretreatment of the promoter.
[0045] (4) The toughening agent of the present invention adopts a core-shell structure, which includes a perlite micropowder core, a microcrystalline wax layer, a rubber layer and a plastic layer from the inside to the outside. The perlite micropowder core is a hard core and can expand by absorbing heat. The microcrystalline wax layer has a low softening point and is ductile. Combined with the rubber layer and the plastic layer, the toughening effect can be comprehensively improved.
[0046] (5) The pearlite micropowder core of the present invention has been treated with a silane coupling agent and can be well combined with the organic microcrystalline wax layer. Then, an anionic emulsifier is added during the preparation of the microcrystalline wax layer, which can be adsorbed with the cationic initiator to promote the formation of a rubber layer on the surface of the microcrystalline wax layer.
[0047] (6) The raw materials for preparing the rubber layer of the toughening agent of the present invention include diallylamine, and the raw materials for preparing the plastic layer include 3,4-epoxy-1-butene, which not only promotes the bonding between the rubber layer and the plastic layer, but also forms a shell plastic with epoxy groups, thereby improving the compatibility of the toughening agent with the toughened matrix (epoxy resin).
[0048] (7) Since the surface of the toughening agent of the present invention is a hard shell, violent collisions can easily destroy the pre-treated accelerator. Therefore, the present invention also performs surface treatments on the toughening agent and the pre-treated accelerator separately so that the two carry the same charge and repel each other. This avoids mutual influence between the two and is also conducive to dispersion. DETAILED DESCRIPTION
[0049] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Example
[0050] This embodiment provides a solvent-free epoxy curing agent, which is composed of 50 parts by weight of benzyl polyamine and 20 parts by weight of polyamine-epoxy adduct. The curing agent is obtained by directly mixing the above raw materials.
[0051] The preparation method of benzyl polyamine is as follows: polyamine, water, potassium hydroxide and methanol are added to a four-necked reaction bottle, and toluene monochloride is slowly added dropwise under a nitrogen atmosphere, and then the temperature is raised to 40°C for reaction for 1 hour. After the reaction is completed, the reaction is filtered, the oil and water are separated, and the benzyl polyamine is obtained by vacuum distillation. The molar ratio of polyamine, potassium hydroxide, fatty alcohol and toluene monochloride is 1:0.8:2:0.7, and the mass ratio of potassium hydroxide to water is 1:3.
[0052] The preparation method of the polyamine-epoxy resin adduct is as follows: take the polyamine into a four-necked reaction bottle, slowly drop bisphenol A glycidyl ether under a nitrogen atmosphere, and then heat to 40°C to react for 1 hour. After the reaction is completed, the polyamine-epoxy resin adduct is obtained; the mass ratio of the polyamine to the bisphenol A glycidyl ether is 1:0.8.
[0053] All of the above polyamines are one or more of aliphatic amines, alicyclic amines and aromatic amine compounds containing two primary amine groups. Example
[0054] Based on Example 1, this example further provides a toughening agent for a solvent-free epoxy curing agent, wherein the toughening agent has a mass fraction of 10 parts in the curing agent. The toughening agent includes a perlite micropowder core, a microcrystalline wax layer, a rubber layer and a plastic layer from the inside to the outside, and the mass ratio thereof is 1:1:3:1.
[0055] The preparation method of the toughening agent is:
[0056] S1. Take perlite powder (particle size is 5μm, loose bulk density is 40kg / m 3), add 5 times the amount of water and silane coupling agent, stir and soak for 30 minutes, then evaporate the water to obtain the pearlite powder core; the mass ratio of pearlite powder to silane coupling agent is 1:0.1;
[0057] S2. According to the mass ratio of 1:0.15, stir the microcrystalline wax (melting point of 65°C) and the carboxylate anion emulsifier evenly, place in an emulsifier (emulsification temperature of 85°C, stirring speed of 2500r / min), add 10 times the amount of deionized water for emulsification, and obtain a microcrystalline wax emulsion;
[0058] S3, placing the pearlite powder core and the microcrystalline wax emulsion in a disperser at 110° C. and dispersing them until the water evaporates to obtain a microcrystalline wax layer;
[0059] S4, add nonionic emulsifier (fatty alcohol polyoxyethylene ether series, the amount added is 10% of deionized water), deionized water (the amount added is 10 times of all raw materials) and the material obtained in step S3 to the reactor, stir evenly, add monomers styrene, butadiene, and diallylamine in a mass ratio of 1:0.4:0.2, stir to emulsify the monomers, then add cationic initiator azobisisobutyramidine hydrochloride (the amount added is 0.06 times of styrene), react at 60°C for 8h, and obtain a rubber layer;
[0060] S5. Add monomers of styrene, 3,4-epoxy-1-butene, and methyl methacrylate to the material obtained in step S4 in a mass ratio of 1:0.3:1, stir to emulsify the monomers, then add a redox initiator (benzoyl peroxide / N,N-dimethylaniline, the added amount is 0.05 times that of styrene), and react at 50° C. for 3 hours to obtain a plastic layer;
[0061] S6, freezing and demulsifying the material obtained in step S5, washing, filtering and vacuum drying to obtain a toughening agent product.
[0062] The rest is the same as Example 1. Example
[0063] This embodiment provides a solvent-free epoxy curing agent, which is composed of 75 parts by weight of benzyl polyamine, 35 parts by weight of polyamine-epoxy adduct, and 10 parts by weight of 2,4,6-tris(dimethylaminomethyl)phenol.
[0064] The preparation method of benzyl polyamine is as follows: polyamine, water, sodium hydroxide and ethanol are added to a four-necked reaction bottle, and toluene monobromide is slowly added dropwise under a nitrogen atmosphere, and then the temperature is raised to 60°C for reaction for 5 hours. After the reaction is completed, the benzyl polyamine is filtered, the oil and water are separated, and the benzyl polyamine is obtained by vacuum distillation. The molar ratio of polyamine, sodium hydroxide, fatty alcohol and toluene monobromide is 1:1:4:0.8, and the mass ratio of sodium hydroxide to water is 1:4.
[0065] The preparation method of the polyamine-epoxy resin adduct is as follows: take the polyamine into a four-necked reaction bottle, slowly drop bisphenol F type glycidyl ether under a nitrogen atmosphere, and then heat to 60°C to react for 3 hours. After the reaction is completed, the polyamine-epoxy resin adduct is obtained; the mass ratio of the polyamine to the bisphenol F type glycidyl ether is 1:1.3. Example
[0066] On the basis of Example 3, this example further provides a pretreatment method of an accelerator, which specifically comprises the following steps:
[0067] (1) Add paraffin (melting point 54°C) and palm wax into 45°C petroleum ether in a mass ratio of 1:2.5:6:1.1 and mix well. Then add a cationic surfactant and mix well. The obtained oil phase is set aside.
[0068] (2) preheating the accelerator to 55°C, and then adding the accelerator dropwise to 3 times the amount of the oil phase obtained in step (1) under stirring (2500 r / min) to obtain an emulsion;
[0069] (3) The emulsion is dispersed in a disperser (500 r / min) and heated (70°C) to evaporate the solvent, thereby completing the pretreatment of the accelerator.
[0070] The preparation method of the cationic surfactant is as follows: fatty acid, benzene and concentrated sulfuric acid are uniformly mixed in a reaction kettle, and then 2,3,4-trihydroxybutyric acid is added dropwise, and the mixture is reacted for 12 hours under heating (85°C) and stirring conditions, and then a mixed solution of anhydrous citric acid and thionyl chloride is added dropwise, and the mixture is reacted for 8 hours under heating (85°C) and stirring conditions, and 4.5 times the amount of deionized water is added to the obtained product, and after uniform mixing, ammonium bicarbonate is added for neutralization reaction, and the cationic surfactant is obtained after filtering and removing impurities; wherein the molar ratio of fatty acid, 2,3,4-trihydroxybutyric acid and anhydrous citric acid is (3-3.3):1:(1-1.4), the amount of concentrated sulfuric acid added is 2-3% of the fatty acid, the amount of thionyl chloride added is 0.5-1.5% of the anhydrous citric acid, and the fatty acid is a long-chain fatty acid.
[0071] The rest is the same as Example 3. Example
[0072] On the basis of Example 3, this example further provides a toughening agent for the solvent-free epoxy curing agent, the mass fraction of which in the curing agent is 15 parts, and the toughening agent includes a perlite micropowder core, a microcrystalline wax layer, a rubber layer and a plastic layer from the inside to the outside, and the mass ratio thereof is 1:1.5:4:2.
[0073] The raw materials for preparing the plastic layer include styrene, 3,4-epoxy-1-butene, methyl methacrylate and a redox initiator in a mass ratio of 1:0.4:1.3:0.08.
[0074] The preparation method of the toughening agent is:
[0075] S1. Take perlite powder (particle size is 7μm, loose bulk density is 55kg / m 3 ), add (7.5 times the amount) water and silane coupling agent, stir and soak for 45 minutes, then evaporate the water to obtain the perlite powder core; the mass ratio of perlite powder to silane coupling agent is 1:0.2;
[0076] S2. According to the mass ratio of 1:0.22, stir the microcrystalline wax (melting point of 70°C) and the sulfonate anion emulsifier evenly, place in an emulsifier (emulsification temperature of 90°C, stirring speed of 3000r / min), add (15 times the amount) of deionized water for emulsification, and obtain a microcrystalline wax emulsion;
[0077] S3, placing the pearlite powder core and the microcrystalline wax emulsion in a disperser at 115° C. and dispersing them until the water evaporates to obtain a microcrystalline wax layer;
[0078] S4, add nonionic emulsifier (isomeric tridecanol polyoxyethyl ether series, the amount added is 13% of deionized water), deionized water (the amount added is 15 times of all raw materials) and the material obtained in step S3 to the reactor, stir evenly, add monomers styrene, butadiene and diallylamine in a mass ratio of 1:0.5:0.3, stir to emulsify the monomers, then add azobisisobutyramidine hydrochloride (the amount added is 0.08 times of styrene), react at 62° C. for 10 hours, and obtain a rubber layer;
[0079] S5. Add monomers of styrene, 3,4-epoxy-1-butene, and methyl methacrylate in a mass ratio of 1:0.4:1.3 to the material obtained in step S4, stir to emulsify the monomers, then add a redox initiator (ammonium persulfate / sodium bisulfite, the added amount is 0.08 times that of styrene), and react at 55° C. for 4 hours to obtain a plastic layer;
[0080] S6, freezing and demulsifying the material obtained in step S5, washing, filtering and vacuum drying to obtain a toughening agent product.
[0081] The rest is the same as Example 3. Example
[0082] This embodiment is a combination of Embodiments 4 and 5. Example
[0083] On the basis of Example 6, this embodiment further provides a method for preparing a solvent-free epoxy curing agent, which specifically comprises the following steps:
[0084] A. According to the mass ratio of 1:0.045, the pretreated accelerator and nano-lignin powder were placed in a disperser at 35°C and dispersed for 1.5 hours to obtain material 1;
[0085] B. Mix lignin sulfonate, sodium silicate and water evenly according to the mass ratio of 1:0.25:4, then add 0.3 times the amount of toughening agent and soak for 40 minutes, then heat and evaporate to obtain material 2;
[0086] C. Evenly mix benzyl polyamine and polyamine-epoxy adduct according to their mass fractions, and then add material 1 and material 2 to obtain the curing agent.
[0087] The rest is the same as Example 6. Example
[0088] This embodiment provides a solvent-free epoxy curing agent, which is composed of 55 parts by weight of benzyl polyamine, 25 parts by weight of polyamine-epoxy adduct, 2 parts by weight of benzyl dimethylamine, and 10 parts by weight of a toughening agent.
[0089] The preparation methods of benzyl polyamine and polyamine-epoxy resin adduct are the same as those in Example 1, and the preparation method of toughening agent is the same as that in Example 2.
[0090] This embodiment also provides a pretreatment method for an accelerator, which specifically comprises the following steps:
[0091] (1) Add paraffin wax (melting point 50°C) and palm wax into chloroform at 40°C in a mass ratio of 1:2:4:0.6, and mix well. Then add a cationic surfactant and mix well. The obtained oil phase is set aside.
[0092] (2) preheating the accelerator to 50° C., and then adding the accelerator dropwise to a volume of the oil phase obtained in step (1) in an amount of 2 times the amount thereof under stirring (2000 r / min) to obtain an emulsion;
[0093] (3) The emulsion is dispersed in a disperser (400 r / min) and heated (65°C) to evaporate the solvent, thereby completing the pretreatment of the accelerator.
[0094] The preparation method of the cationic surfactant is as follows: fatty acid, benzene and concentrated sulfuric acid are uniformly mixed in a reaction kettle, and then 2,3,4-trihydroxybutyric acid is added dropwise, and the mixture is reacted for 8 hours under heating (80°C) and stirring conditions, and then a mixed solution of anhydrous citric acid and thionyl chloride is added dropwise, and the mixture is reacted for 6 hours under heating (80°C) and stirring conditions, and 3-6 times the amount of deionized water is added to the obtained product, and ammonium bicarbonate is added to neutralize the product after uniform mixing, and the cationic surfactant is obtained after filtering and removing impurities; wherein the molar ratio of fatty acid, 2,3,4-trihydroxybutyric acid and anhydrous citric acid is 3:1:1, the amount of concentrated sulfuric acid added is 2% of the fatty acid, and the amount of thionyl chloride added is 0.5% of the anhydrous citric acid.
[0095] This embodiment also provides a method for preparing a solvent-free epoxy curing agent, which specifically comprises the following steps:
[0096] A. According to the mass ratio of 1:0.03, the pretreated accelerator and nano-lignin powder were placed in a disperser at 30°C and dispersed for 1 hour to obtain material 1;
[0097] B. Mix lignin sulfonate, sodium silicate and water evenly in a mass ratio of 1:0.1:3, then add 0.2 times the amount of toughening agent and soak for 30 minutes, then heat and evaporate to obtain material 2;
[0098] C. Evenly mix benzyl polyamine and polyamine-epoxy adduct according to their mass fractions, and then add material 1 and material 2 to obtain the curing agent. Example
[0099] The present embodiment provides a solvent-free epoxy curing agent, which is composed of 100 parts by weight of benzyl polyamine, 50 parts by weight of polyamine-epoxy adduct, 20 parts by weight of o-hydroxybenzyl dimethylamine, and 20 parts by weight of toughening agent.
[0100] The preparation method of benzyl polyamine is as follows: polyamine, water, lithium hydroxide and isopropanol are added to a four-necked reaction bottle, and toluene monobromide is slowly added dropwise under a nitrogen atmosphere, and then the temperature is raised to 80°C for reaction for 10 hours. After the reaction is completed, the benzyl polyamine is filtered, the oil and water are separated, and the benzyl polyamine is obtained by vacuum distillation. The molar ratio of polyamine, lithium hydroxide, isopropanol and toluene monobromide is 1:1.2:6:0.7, and the mass ratio of lithium hydroxide to water is 1:5.
[0101] The preparation method of the polyamine-epoxy resin adduct is as follows: take the polyamine into a four-necked reaction bottle, slowly dropwise add cardanol glycidyl ether under a nitrogen atmosphere, and then heat to 80°C to react for 6 hours. After the reaction is completed, the polyamine-epoxy resin adduct is obtained; the mass ratio of the polyamine to the cardanol glycidyl ether is 1: (0.8-1.8).
[0102] This embodiment also provides a pretreatment method for an accelerator, which specifically comprises the following steps:
[0103] (1) Add paraffin (melting point 60°C) and palm wax into 50°C petroleum ether in a mass ratio of 1:3:8:1.6 and mix well. Then add a cationic surfactant and mix well. The obtained oil phase is set aside.
[0104] (2) preheating the accelerator to 60° C., and then adding the accelerator dropwise to 4 times the amount of the oil phase obtained in step (1) under stirring (3000 r / min) to obtain an emulsion;
[0105] (3) The emulsion is dispersed in a disperser (600 r / min) and heated (75°C) to evaporate the solvent, thereby completing the pretreatment of the accelerator.
[0106] The preparation method of the cationic surfactant is as follows: fatty acid, benzene and concentrated sulfuric acid are uniformly mixed in a reaction kettle, and then 2,3,4-trihydroxybutyric acid is added dropwise, and the mixture is reacted for 16 hours under heating (90°C) and stirring conditions, and then a mixed solution of anhydrous citric acid and thionyl chloride is added dropwise, and the mixture is reacted for 10 hours under heating (90°C) and stirring conditions, and 3-6 times the amount of deionized water is added to the obtained product, and ammonium bicarbonate is added to neutralize the product after uniform mixing, and the cationic surfactant is obtained after filtering and removing impurities; wherein the molar ratio of fatty acid, 2,3,4-trihydroxybutyric acid and anhydrous citric acid is 3.3:1:1.4, the amount of concentrated sulfuric acid added is 3% of the fatty acid, and the amount of thionyl chloride added is 1.5% of the anhydrous citric acid.
[0107] This embodiment also provides a toughening agent for the solvent-free epoxy curing agent, which includes a perlite micro powder core, a microcrystalline wax layer, a rubber layer and a plastic layer from the inside to the outside, and the mass ratio thereof is 1:2:5:3.
[0108] The raw materials for preparing the plastic layer include styrene, 3,4-epoxy-1-butene, methyl methacrylate and a redox initiator in a mass ratio of 1:0.5:1.6:0.1.
[0109] The preparation method of the toughening agent is:
[0110] S1. Take perlite powder (particle size is 10μm, loose bulk density is 70kg / m 3 ), add (10 times the amount) water and silane coupling agent, stir and soak for 60 minutes, then evaporate the water to obtain the pearlite powder core; the mass ratio of pearlite powder to silane coupling agent is 1:0.3;
[0111] S2. According to the mass ratio of 1:0.3, stir the microcrystalline wax (melting point of 75°C) and the carboxylate anionic emulsifier evenly, place in an emulsifier (emulsification temperature of 95°C, stirring speed of 3500r / min), add (20 times the amount) of deionized water for emulsification, and obtain a microcrystalline wax emulsion;
[0112] S3, placing the pearlite powder core and the microcrystalline wax emulsion in a disperser at 120° C. and dispersing them until the water evaporates to obtain a microcrystalline wax layer;
[0113] S4, add nonionic emulsifier (alkylphenol polyoxyethylene ether series, the amount added is 16% of deionized water), deionized water (the amount added is 20 times of all raw materials) and the material obtained in step S3 to the reactor, stir evenly, add monomers styrene, butadiene, and diallylamine in a mass ratio of 1: 0.6: 0.4, stir to emulsify the monomers, then add azobisisobutyramidine hydrochloride (the amount added is 0.1 times of styrene), and react at 65° C. for 12 hours to obtain a rubber layer;
[0114] S5. Add monomers of styrene, 3,4-epoxy-1-butene, and methyl methacrylate to the material obtained in step S4 in a mass ratio of 1:0.5:1.6, stir to emulsify the monomers, then add a redox initiator (isopropylbenzene hydroperoxide / tetraethyleneimine, the added amount is 0.1 times that of styrene), and react at 60° C. for 5 hours to obtain a plastic layer;
[0115] S6, freezing and demulsifying the material obtained in step S5, washing, filtering and vacuum drying to obtain a toughening agent product.
[0116] This embodiment also provides a method for preparing a solvent-free epoxy curing agent, which specifically comprises the following steps:
[0117] A. According to the mass ratio of 1:0.06, the pretreated accelerator and nano-lignin powder were placed in a disperser at 40°C and dispersed for 1-2 hours to obtain material 1;
[0118] B. Mix lignin sulfonate, sodium silicate and water evenly in a mass ratio of 1:0.4:5, then add 0.4 times the amount of toughening agent and soak for 50 minutes, then heat and evaporate to obtain material 2;
[0119] C. Evenly mix benzyl polyamine and polyamine-epoxy adduct according to their mass fractions, and then add material 1 and material 2 to obtain the curing agent.
[0120] Comparative Example 1
[0121] The difference between this comparative example and Example 7 is that the oil phase in step (1) of the accelerator pretreatment method does not include paraffin.
[0122] Comparative Example 2
[0123] The difference between this comparative example and Example 7 is that palm wax is not included in the oil phase of the accelerator pretreatment step (1).
[0124] Comparative Example 3
[0125] The difference between this comparative example and Example 7 is that in the step (1) of the pretreatment method of the accelerator, petroleum ether is replaced by benzene.
[0126] Comparative Example 4
[0127] The difference between this comparative example and Example 7 is that in the step (1) of the accelerator pretreatment method, the mass ratio of paraffin wax to palm wax is 1:1.5.
[0128] Comparative Example 5
[0129] The difference between this comparative example and Example 7 is that in the step (1) of the accelerator pretreatment method, the mass ratio of paraffin wax to palm wax is 1:3.5.
[0130] Comparative Example 6
[0131] The difference between this comparative example and Example 7 is that the oil phase in step (1) of the accelerator pretreatment method does not include a cationic surfactant.
[0132] Comparative Example 7
[0133] The difference between this comparative example and Example 7 is that the cationic surfactant in the pretreatment method of the accelerator is a conventional quaternary ammonium salt type cationic surfactant containing a C10-C18 long-chain alkyl group.
[0134] Comparative Example 8
[0135] The difference between this comparative example and Example 8 is that the toughening agent is a common toughening agent polyimide.
[0136] Comparative Example 9
[0137] The difference between this comparative example and Example 8 is that the toughening agent includes a rubber layer and a plastic layer in sequence from the inside to the outside.
[0138] Comparative Example 10
[0139] The difference between this comparative example and Example 8 is that the toughening agent does not include a microcrystalline wax layer.
[0140] Comparative Example 11
[0141] The difference between this comparative example and Example 8 is that in step S1 of the method for preparing the toughening agent, the perlite powder is replaced with silica powder.
[0142] Comparative Example 12
[0143] The difference between this comparative example and Example 8 is that in step S1 of the method for preparing the toughening agent, no silane coupling agent is added.
[0144] Comparative Example 13
[0145] The difference between this comparative example and Example 8 is that in step S4 of the method for preparing the toughening agent, the monomer diallylamine is not added.
[0146] Comparative Example 14
[0147] The difference between this comparative example and Example 8 is that in step S5 of the method for preparing the toughening agent, the monomer 3,4-epoxy-1-butene is not added.
[0148] Comparative Example 15
[0149] The difference between this comparative example and Example 9 is that in step A of the preparation method of the solvent-free epoxy curing agent, the temperature of the disperser is 25°C.
[0150] Comparative Example 16
[0151] The difference between this comparative example and Example 9 is that in step A of the preparation method of the solvent-free epoxy curing agent, the temperature of the disperser is 45°C.
[0152] Comparative Example 17
[0153] The difference between this comparative example and Example 9 is that in step A of the preparation method of the solvent-free epoxy curing agent, no nano-lignin powder is added.
[0154] Comparative Example 18
[0155] The difference between this comparative example and Example 9 is that in step B of the preparation method of the solvent-free epoxy curing agent, no lignin sulfonate is added.
[0156] Comparative Example 19
[0157] The difference between this comparative example and Example 9 is that in step B of the preparation method of the solvent-free epoxy curing agent, no sodium silicate is added.
[0158] The curing agents prepared in Examples 1-9 and Comparative Examples 1-19 of the present invention, as well as commercially available solvent-free epoxy curing agents, were mixed with bisphenol A epoxy resin (epoxy value was 0.4) at a ratio of n (epoxy group) / n (active hydrogen of amine group) = 1 / 1 to prepare a two-component epoxy coating. The paint film products were prepared in accordance with GB / T 1727-1992 "General Preparation Method for Paint Film" and tested. The curing performance results are shown in Table 1.
[0159] Table 1
[0160] Experimental Grouping Hardness / H Adhesion Flexibility / mm Impact resistance / cm Water resistance Curing surface drying time / h Test Method GB / T6739-2006 GB / T 1720-1979 GB / T 1731-1993 GB / T 1732-1993 GB / T 1733-1993 — Result judgment H-9H, increasing hardness Level 1-7, the adhesion decreases in sequence Minimum shaft diameter without causing paint film damage Maximum height without causing damage to the paint film At least two of the three test panels should meet the requirements of the product standard to be qualified — Commercially available solvent-free epoxy curing agent 4 H Level 3 ≤3 50 qualified 4.0 Example 1 4 H Level 3 ≤3 54 qualified 4.0 Example 2 5 H Level 2 ≤1 61 qualified 4.0 Example 3 4 H Level 3 ≤3 55 qualified 3.5 Example 4 5H Level 2 ≤3 63 qualified 2.5 Example 5 5 H Level 2 ≤2 60 qualified 4.0 Example 6 5 H Level 2 ≤2 65 qualified 3.5 Example 7 6H Level 1 ≤1 74 qualified 2.0 Example 8 6H Level 1 ≤1 70 qualified 2.0 Example 9 6H Level 1 ≤1 71 qualified 2.0 Comparative Example 1 5H Level 2 ≤2 66 qualified 2.5 Comparative Example 2 5H Level 2 ≤2 67 qualified 2.5 Comparative Example 3 5H Level 2 ≤2 65 qualified 3.0 Comparative Example 4 5H Level 2 ≤2 69 qualified 2.5 Comparative Example 5 5H Level 2 ≤2 68 qualified 2.5 Comparative Example 6 4H Level 3 ≤2 65 qualified 3.0 Comparative Example 7 5H Level 2 ≤2 65 qualified 3.0 Comparative Example 8 5H Level 2 ≤3 61 qualified 2.0 Comparative Example 9 5H Level 2 ≤2 63 qualified 2.0 Comparative Example 10 5H Level 2 ≤2 64 qualified 2.0 Comparative Example 11 5H Level 2 ≤2 65 qualified 2.0 Comparative Example 12 5H Level 2 ≤2 65 qualified 2.0 Comparative Example 13 5H Level 2 ≤2 66 qualified 2.0 Comparative Example 14 5H Level 2 ≤2 66 qualified 2.0 Comparative Example 15 5H Level 2 ≤1 64 qualified 3.0 Comparative Example 16 5H Level 2 ≤1 65 qualified 3.0 Comparative Example 17 5H Level 2 ≤2 62 qualified 3.0 Comparative Example 18 5H Level 2 ≤2 63 qualified 3.0 Comparative Example 19 5H Level 2 ≤2 63 qualified 2.5
[0161] As can be seen from Table 1 above, the solvent-free epoxy curing agent prepared by the present invention has excellent performance indicators, most of which are better than commercially available products, especially Examples 7-9, with a hardness of 6H, an adhesion of level 1, a flexibility of ≤1mm, an impact resistance of 70-74cm, excellent water resistance, and a curing surface drying time of 2h, showing good curing performance.
[0162] Among them, on the basis of Example 3, Example 4 pre-treats the accelerator, so that the curing time of the curing agent is shortened and other curing properties are also improved; Example 5 adds a toughening agent, and its flexibility and other curing properties are improved.
[0163] Example 6 combines the technical solutions in Examples 4 and 5, but because the pretreated accelerator is easily affected by the toughening agent, the final curing surface drying time and other curing properties are not significantly improved or even decreased. On the basis of Example 6, when preparing the curing agent, Example 7 also simultaneously performs surface treatment on the toughening agent and the pretreated accelerator, so that the comprehensive performance of the curing agent is improved.
[0164] The curing agents prepared in Examples 3, 5, 7-9 and Comparative Examples 8-14 of the present invention, as well as commercially available solvent-free epoxy curing agents, were formulated with bisphenol A epoxy resin into two-component epoxy coatings. Impact strength, flexural strength, and elongation at break were tested in accordance with relevant national standards. The results are shown in Table 2.
[0165] Table 2
[0166] Experimental Grouping <![CDATA[Izod impact strength of cantilever beam / (kJ / m 2 )]]> Bending strength (MPa) Tensile strength (MPa) Test Method GB / T 1043-1993 GB / T 9341-2000 GB / T 1040-92 Commercially available curing agent 20.1 102.4 90.8 Example 3 24.6 106.3 100.9 Example 5 31.1 119.2 133.7 Example 7 36.5 125.3 148.5 Example 8 36.1 124.5 139.2 Example 9 35.8 124.9 142.8 Comparative Example 8 28.5 112.3 115.6 Comparative Example 9 29.7 115.5 120.7 Comparative Example 10 30.2 116.8 123.5 Comparative Example 11 32.4 119.7 129.1 Comparative Example 12 30.1 118.6 130.4 Comparative Example 13 31.2 120.3 128.7 Comparative Example 14 32.5 120.8 132.3
[0167] As can be seen from Table 2 above, the impact strength, flexural strength and tensile strength of the solvent-free epoxy curing agents prepared in Examples 3, 5, 7-9 of the present invention are better than those of commercially available products. On the basis of Example 3, the present invention prepares a toughening agent and adds it to the curing agent, and its impact strength, flexural strength and tensile strength are significantly improved.
[0168] In particular, Examples 7, 8, and 9 performed excellently, with an impact strength of 35.8 kJ / m 2 The bending strength is above 124.5 MPa, and the tensile strength is above 139.2 MPa. The curing agent of the present invention exhibits a good toughening effect.
[0169] The beneficial effect of the present invention is that the solvent-free epoxy curing agent and the preparation method thereof provided by the present invention respectively designs the amine curing main body, the toughening agent and the accelerator in the curing agent, which can effectively improve the comprehensive performance of the curing agent.
[0170] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A solvent-free epoxy curing agent, characterized in that: The invention comprises the following raw materials in parts by weight: 50-100 parts of benzyl polyamine, 20-50 parts of polyamine-epoxy adduct, 0-20 parts of accelerator and 10-20 parts of toughening agent; the benzyl polyamine is prepared by the following steps: polyamine, water, metal hydroxide and fatty alcohol are put into a four-necked reaction bottle, toluene monohalide is slowly added dropwise under nitrogen atmosphere, and then the temperature is raised to 40-80° C. to react for 1-10 hours, and after the reaction is completed, the benzyl polyamine is filtered, oil-water is separated and distilled under reduced pressure to obtain the benzyl polyamine; The toughening agent comprises a pearlite micro powder core, a microcrystalline wax layer, a rubber layer and a plastic layer in sequence from the inside to the outside, and the mass ratio thereof is 1:(1-2):(3-5):(1-3).
2. The solvent-free epoxy curing agent according to claim 1, characterized in that: The promoter is selected from one of 2,4,6-tris(dimethylaminomethyl)phenol, benzyldimethylamine, triethylamine, triethanolamine and o-hydroxybenzyldimethylamine; the molar ratio of polyamine, metal hydroxide, fatty alcohol and toluene monohalide is 1:(0.8-1.2):(2-6):(0.7-0.9); the mass ratio of metal hydroxide to water is 1:(3-5).
3. The solvent-free epoxy curing agent according to claim 1, characterized in that: The polyamine-epoxy resin adduct is prepared by the following steps: taking a polyamine into a four-necked reaction bottle, slowly dropping an epoxy resin in a nitrogen atmosphere, and then heating to 40-80° C. to react for 1-6 hours. After the reaction is completed, the polyamine-epoxy resin adduct is obtained; the mass ratio of the polyamine to the epoxy resin is 1:(0.8-1.8).
4. The solvent-free epoxy curing agent according to claim 1, characterized in that: The raw materials for preparing the perlite micropowder core include perlite micropowder and silane coupling agent in a mass ratio of 1:(0.1-0.3); the raw materials for preparing the microcrystalline wax layer include microcrystalline wax and anionic emulsifier in a mass ratio of 1:(0.15-0.3); the raw materials for preparing the rubber layer include styrene, butadiene, diallylamine, and azobisisobutyramidine hydrochloride in a mass ratio of 1:(0.4-0.6):(0.2-0.4):(0.06-0.1); the raw materials for preparing the plastic layer include styrene, 3,4-epoxy-1-butene, methyl methacrylate, and redox initiator in a mass ratio of 1:(0.3-0.5):(1-1.6):(0.05-0.1).
5. The solvent-free epoxy curing agent according to claim 1, characterized in that: The preparation method of the toughening agent is: S1. Take perlite powder, add water and silane coupling agent, stir and soak for 30-60 minutes, then evaporate the water to obtain perlite powder core; S2, stirring the microcrystalline wax and anionic emulsifier evenly, placing in an emulsifier, adding deionized water for emulsification, and obtaining a microcrystalline wax emulsion; S3, placing the pearlite powder core and the microcrystalline wax emulsion in a disperser at 110-120° C. and dispersing until the water evaporates to obtain a microcrystalline wax layer; S4, adding a nonionic emulsifier, deionized water and the material obtained in step S3 to a reaction kettle, stirring evenly, adding monomers styrene, butadiene and diallylamine, stirring to emulsify the monomers, and then adding azobisisobutyramidine hydrochloride, reacting at 60-65° C. for 8-12 hours to obtain a rubber layer; S5, adding monomers of styrene, 3,4-epoxy-1-butene, and methyl methacrylate to the material obtained in step S4, stirring to emulsify the monomers, and then adding a redox initiator, reacting at 50-60° C. for 3-5 hours to obtain a plastic layer; S6, freezing and demulsifying the material obtained in step S5, washing, filtering and vacuum drying to obtain a toughening agent product.
6. A method for pretreating an accelerator in a solvent-free epoxy curing agent according to claim 1, characterized in that: The specific steps include: (1) adding paraffin wax and palm wax to a solvent and mixing them evenly, then adding an anionic surfactant and mixing them evenly, and the obtained oil phase is used for standby; (2) preheating the accelerator and adding it dropwise to the oil phase obtained in step (1) under stirring to obtain an emulsion; (3) The emulsion is dispersed in a disperser and heated to evaporate the solvent, thereby completing the pretreatment of the accelerator.
7. The pretreatment method of the accelerator according to claim 6, characterized in that: In step (1), the melting point of paraffin is 50-60° C., the solvent is petroleum ether or chloroform, and the mass ratio of paraffin, palm wax, solvent and anionic surfactant is 1:(2-3):(4-8):(0.6-1.6); and in step (2), the mass ratio of accelerator to oil phase is 1:(2-4).
8. The pretreatment method of the accelerator according to claim 6, characterized in that: The preparation method of the anionic surfactant comprises the following steps: evenly mixing fatty acid, benzene and concentrated sulfuric acid in a reaction kettle, then dropping 2,3,4-trihydroxybutyric acid, reacting for 8-16 hours under heating and stirring conditions, then dropping a mixed solution of anhydrous citric acid and thionyl chloride, reacting for 6-10 hours under heating and stirring conditions, adding 3-6 times amount of deionized water to the obtained product, mixing evenly, adding ammonium bicarbonate to carry out neutralization reaction, filtering and removing impurities to obtain the anionic surfactant; wherein the molar ratio of fatty acid, 2,3,4-trihydroxybutyric acid and anhydrous citric acid is (3-3.3):1:(1-1.4), the amount of concentrated sulfuric acid added is 2-3% of the fatty acid, and the amount of thionyl chloride added is 0.5-1.5% of the anhydrous citric acid.
9. A method for preparing a solvent-free epoxy curing agent according to any one of claims 1 to 8, characterized in that: The specific steps include: A. Place the pretreated accelerator and nano-lignin powder in a disperser at 30-40°C and disperse for 1-2 hours to obtain material 1; B. Mix lignin sulfonate, sodium silicate and water evenly, then add 0.2-0.4 times the amount of toughening agent and soak for 30-50 minutes, then heat and evaporate to obtain material 2; C. Evenly mix the benzyl polyamine and the polyamine-epoxy adduct according to the mass fractions, and then add material 1 and material 2 to obtain a curing agent; The mass ratio of the pretreated accelerator to the nano-lignin powder in step A is 1:(0.03-0.06), and the mass ratio of lignin sulfonate, sodium silicate and water in step B is 1:(0.1-0.4):(3-5).
Citation Information
Patent Citations
Preparation of amine terminated polyether aqueous epoxy hardener
CN101348561A
Ternary surface active agent adopting 1,1,1-tri(hydroxymethyl) ethane as link group, and preparation method of ternary surface active agent
CN104645876A